DETERMINAN MOTIVASI INTERNAL TERHADAP KINERJA - Fitria Nur Anggraeni (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
Excellent service is proof of performance, but mood and character have an influence on that achievement. Therefore, maintaining motivation is a necessity in carrying out tasks, so that employees have a strength to be consistent on work standards. This study is a reflection of interest in reviewing internal motivational factors for performance. The object of this study is retail employees in the Jabodetabek area with a sample size of 400. The research method uses quantitative by distributing questionnaires and interviews. The analysis model uses a regression equation, with reasons to estimate performance changes in the future. These findings indicate that the characteristics become a dominant motivational factor in explaining performance. The characteristic in question is perseverance, in every situation employees always present work spirit, patience, and no strings attached. Keywords: Persevering, Positive Thinking, Determination, Performance